Back to the future: Transplanting the chloroplast TrxF–FBPase–SBPase redox system to cyanobacteria - García-Cañas, Raquel; Florencio, Francisco J.; López-Maury, Luis (Frontiers in Plant Science, 2022)
Fructose-1, 6-bisphosphatase (FBPase) and sedoheptulose-1, 7-bisphosphatase (SBPase) are two essential activities in the Calvin-Benson-Bassham Cycle that catalyse two irreversible reactions and are key for proper regulation and functioning of the cycle. These two activities are codified by a single gene in all cyanobacteria, although some cyanobacteria contain an additional gene coding for a FBPase. Mutants lacking the gene coding for SBP/FBPase protein are not able to grow photoautotrophically and require glucose to survive. As this protein presents both activities, we have tried to elucidate which of the two are required for photoautrophic growth in Synechocystis sp PCC 6803. For this, the genes coding for plant FBPase and SBPase were introduced in a SBP/FBPase mutant strain, and strains were tested for growth in the absence of glucose. Ectopic expression of only a plant SBPase gene didn't allow growth in the absence of glucose although allowed mutation of both Synechocystis’ FBPase genes. When both plant FBPase and SBPase genes were expressed photoautrophic growth of the SBP/FBPase mutants was restored. This complementation was partial as the strain only grew in low light but growth was impaired at higher light intensities. Redox regulation of the Calvin-Benson-Bassham Cycle is essential to properly coordinate light reactions to carbon fixation in the chloroplast. Two of the best characterised proteins that are redox regulated in the cycle are FBPase and SBPase. These two proteins are targets of the FTR-Trx redox system with Trx f being the main reductant in vivo. Introduction of the TrxF gene improves growth of the complemented strain, suggesting that the redox state of the proteins may be the cause of this phenotype. The redox state of the plant proteins was also checked in these strains, and it shows that the cyanobacterial redox system is able to reduce all of them (SBPase, FBPase and TrxF) in a light dependent manner. Thus, the TrxF-FBPase-SBPase plant chloroplast system is active in cyanobacteria despite these organisms do not contain proteins related to them. Furthermore, our system opens the possibility to study specificity of the Trx system in vivo without the complication of the different isoforms present in plants.